2015
DOI: 10.3923/rjes.2015.302.306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Growing Media on the Growth and Development of Zinnia (Zinnia elegans) under the Agro-Climatic Condition of Jiroft

Abstract: Zinnia elegans, an annual flowering plant of the genus Zinnia, is one of the best known zinnias. Present study was conducted to evaluate the effect of different growing media on the growth and flowering of Zinnia elegans. Seven different growth media including coconut compost, silt, soil loam, leaf manure, (leaf manure+silt; 2:1), (coconut compost+soil loam; 1:1) and (leaf manure+soil loam+silt; 1:1:1) were used for growing Zinnia. The experiment was laid out in Complete Randomized Design (CRD) giving equal im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 6 publications
1
11
0
2
Order By: Relevance
“…On the other hand, the lowest number of leaves and branches per plant was found in plants grown in peat + sand (1:2) medium, this result was true in both seasons. Similar results were obtained by Riaz et al, (2014) and Sardoei and Shahdadneghad (2015) on Zinnia. In this respect, Dubey et al, (2013) concluded that soil + sewage sludge as growing media for petunia have high positive effect and significantly improved most vegetative growth character included number of leaves and branches per plant.…”
Section: Vegetative Growthsupporting
confidence: 88%
“…On the other hand, the lowest number of leaves and branches per plant was found in plants grown in peat + sand (1:2) medium, this result was true in both seasons. Similar results were obtained by Riaz et al, (2014) and Sardoei and Shahdadneghad (2015) on Zinnia. In this respect, Dubey et al, (2013) concluded that soil + sewage sludge as growing media for petunia have high positive effect and significantly improved most vegetative growth character included number of leaves and branches per plant.…”
Section: Vegetative Growthsupporting
confidence: 88%
“…Addition of organic manure to the inert substrate is essential to supply nutrients to the plants (Khan et al, 2006). According to Sardoei et al, (2014) selection of suitable media is essential for the flowering potted plants in order to improve the aesthetic value and marketing potential. Keeping in view the importance of substrates, the present study was conducted to standardize the growth, flowering and suitability of tuberose var.…”
Section: Issn: 2319-7706 Volume 8 Number 01 (2019)mentioning
confidence: 99%
“…), species of the Asteraceae family of great potential in Brazil that presents an immense diversity of colors and petal shapes (Franzen et al, 2016), there are few studies about the longevity and postharvest characteristics of its flowers. Parameters such as density, porosity and water retention capacity of the growth substrate are known to influence the initial development of zinnia, and its floral quality (Pê go et al, 2019;Sardoei et al, 2014). As regards the influence of irrigation management, Heidari et al (2016) illustrated that growing plants under low water availability in arid or semi-arid climates leads to a decrease in the postharvest durability of zinnia flowers, cv.…”
Section: Introductionmentioning
confidence: 99%